Truth Commissions and the Recognitions of State Crime - Stanley, Elizabeth (The British journal of criminology, 2005)
This article seeks to analyse the conditions by which state crime comes to be recognized or mis-recognized, particularly through truth commission proceedings. Truth commissions, established in transitions to democracy, often provide the most authoritative documents on state crime. While this recognition of state crime presents an opportunity to challenge popular perceptions and power relations, this approach is commonly detached from the linked imperative of social justice. Building on the work of Nancy Fraser (1997; 2000; 2003) and the author's own primary research, the article details that while truth commissions expose a partial truth' of state crime, they inhibit recognition of status subordination that would allow a challenge to institutionalized patterns of inequality, discrimination and oppression